Triangular block bridge method for surgical treatment of complex proximal humeral fractures: theoretical concept, surgical technique and clinical results. (October 2017) - Russo, Raffaele; D'Auria, Daniela; Ciccarelli, Michele; Della Rotonda, Giuseppe; D'Elia, Gesualdo; Siciliano, Bruno
Abstract: Introduction: Criteria for classification, indication and choice of a surgical device to treat proximal humeral fractures are still controversial. We report an original technique based on a mechanical concept with a structural principle of a triangle as a rigid body applied to the humeral head fractures in association with other devices. This retrospective study aims to describe in detail the surgical technique and results at long time follow up. Methods and Material: We analysed two series of 101 patients with proximal humeral fractures (mean age, 52.9 y; range 19–78 y) treated between 2001 and 2012 reporting the clinical and radiological results. In the first series of 23 cases (mean age 51.4 y, range 35–74 y) we used as support a bone piece taken from allograft or autologous tricortical iliac crest and shaped as a triangular pyramid during the operation; while in the second series of 78 cases (mean age 53.6 years, range 29–78 years, SD 13.5 years) a triangular titanium cage was used in 69 patients while in 9 allograft or bone substitute was used as augmentation. An analytical retrospective study was done to understand the mechanical function of medial augmentation composed by a solid body in association with different types of synthesis to stabilize properly a proximal humeral fracture. Results: We obtained excellent and good results in 83, 2% of patients, fair in 12, 8% and bad in 4% in terms of active anterior elevation, external and internal rotation, pain and strength according to Constant and DASH score. Conclusion: A medial solid body, especially in titanium material and shaped as trapezoidal/pyramidal form used to fill the secondary bone loss in complex instable proximal humeral fracture, allows an anatomic reduction and stable fixation in association with simple and more complex tools and it provides a better biomechanical environment for union and maintenance of alignment.